The Convergence of Minds and Machines: A Bibliometric Analysis into HRM and Industry 4.0 Dynamics (Journal of Informatics Education and Research, 2024)
Purpose: With the trends in smart technology in Industry 4.0 there have been notable changes in industries as well as towards human resources. This work aims to examine the creation of symbiosis between the human brain and intelligent machines in the area of HRM and Innovation 4.0. The main goal is to perform a bibliometric analysis of the literature, which will reveal emerging research trends, influential authors, pertinent nations, and potential future research directions in the area of HRM and Industry 4.0.Methodology: An extensive bibliometric analysis of 176 articles drawn from the Scopus database was conducted. For analysis, the study utilized Biblioshiny and VOSviewer to identify the research hotspots, subject areas, and emergent trends. We employed co-occurrence and citation analysis to uncover the intellectual structure of researchResults: The findings of the study revealed that Industry 4.0 and HRM are vibrant and expanding fields. The adoption of disruptive technologies related to Industry 4.0 is altering workplace culture and HR procedures, enabling organizations to blend human insight with machine-driven analytics, and creating more adaptive, responsive, and financially efficient HR systems. Along with descriptive analysis, the research also unveiled a shift in focus toward sustainable HR practices, emphasizing long-term financial stability and talent retention.Implications: This study has implications for both academia and practitioners by offering new perspectives on human dynamics in Industry 4.0. It not only considers the constant dynamics of Industry 4.0 regarding the subject area of HRM but also highlights the essence of the interaction between disruptive technology and human resource practices in the digital environment. Therefore, the study provides guidelines on the further research direction as well as gaps required to conduct a further investigation of this critical trend of technology and human resources management intersection.